Synthesis of polycrystalline gallium oxide solar-blind ultraviolet photodetector by Aerosol Deposition - Jang, Han Eol; Cho, Hyeon Ho; Yu, Hak Ki; Choi, Jae Young; Park, Jae Hyuk (Journal of the European Ceramic Society, 2023)
An aerosol deposition method was used to fabricate a solar-blind photodetector (for UV-C) using thin films of β-Ga2O3, which is a wide-bandgap oxide material. The Ga2O3 films deposited at room temperature presented a polycrystalline structure and a thickness of approximately 4 µm and showed a high transmittance of approximately 70–80 % in the visible region; the transmittance was approximately 60–80 % even after heat treatment up to a 800 °C. The Ga2O3 films that were post-annealed at a temperature of 800 °C showed an Iphoto/Idark ratio of approximately 40,000 in the solar-blind region with a light source of 254 nm, together with very good light detection characteristics (initial rising and decay times of 0.45 s and 0.13 s, respectively). Because of the good performances observed for the Ga2O3 thin films even at extreme conditions, they exhibit a high potential for use as photodetectors in several applications.
Keywords: Aerosol deposition; Aerosol deposition method; Polycrystalline; Solar blind ultraviolet; Solar-blind photodetectors; Thin-films; Ultra-violet photodetectors; UV-C; Wide-band-gap; Β-ga2O3 thin film; Aerosol deposition; Solar-blind photodetector; UV-C; β-Ga2O3 thin film